Sustainability UMKM Cirebon: Literasi Keuangan, Fintech Lending, Digitalisasi, dan Strategi Pemasaran - Gytha Nurhana Dhea Praadha Gitama; Dessy Kumala Dewi; Ilham Hidayat; Ridho Fardani; Adilla Sukma (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - The purpose of this study is to examine and obtain empirical evidence regarding the influence of financial literacy, fintech lending, digitalization, and marketing strategies on the sustainability of MSMEs in Cirebon City, including the moderating role of digitalization and marketing strategies. Method - This research method uses a quantitative approach using Structural Equation Modeling (SEM) analysis tools based on Partial Least Squares (PLS) using SmartPLS software. The analysis was conducted through validity, reliability, multicollinearity, R-square tests, and hypothesis testing to examine the relationships between variables in the research model. Main Findings - The main findings of the study indicate that financial literacy and marketing strategies have a significant influence on the sustainability of MSMEs in Cirebon City. Conversely, fintech lending and digitalization do not have a direct impact on business aspirations, as their utilization is still limited to short-term needs and technical aspects. These results indicate that MSMEs' aspirations are more determined by internal capacity in the form of financial knowledge and adaptive marketing strategies than simply access to financing and adoption of digital technology. Theory and Practical Implications - Theoretically, this study strengthens the literature that financial literacy and marketing strategies are key factors in explaining MSME sustainability, while fintech lending and digitalization are only effective when integrated with the internal capacity of business actors. From a policy perspective, these results suggest the need for local governments and related institutions to prioritize financial education programs and digital marketing strategy assistance to optimize the impact of financing and technology on MSME sustainability. Novelty - The novelty of this research lies in the integration of financial literacy, fintech lending, digitalization, and marketing strategy variables into one model of MSME sustainability in Cirebon City, as well as testing the moderating role of digitalization and marketing strategy, which has rarely been studied in previous studies. Keywords: Financial Literacy, Fintech Lending, Digitalization, Marketing Strategy, MSME Sustainability